Analisis Pendapatan Usaha Pengolahan Ikan Asin pada Usaha Rumah Tangga di Bontang Kuala, Kalimantan Timur - Kurniawan A., Erwin; Hasid, Zamruddin; Busari, Arfiah (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Indonesia is an archipelagic nation known as a maritime area with natural riches in fisheries, such as marine biota and marine tourism. Since 1952, the progress of Bontang Kuala City has been supported by various industrial centers that utilize fishery products. This study aims to study financial aspects, including income, expenses, efficiency, and profits in the salted fish processing business managed by residents who live around the coastal area of Bontang City. The instruments applied to analyze data are analysis of business efficiency, costs, revenues, and profits. The objectivity of the study relies on the method of direct interviews with informants. The study results show that the average fixed and variable monthly costs, average revenue, and average monthly profit are